The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1186/s12903-015-0024-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect on enamel shear bond strength of adding microsilver and nanosilver particles to the primer of an orthodontic adhesive

Abstract: BackgroundThe objective of this study was to determine whether the addition of microsilver or nanosilver particles to an orthodontic primer affects shear bond strength (SBS) and bracket/adhesive failure.MethodsBovine incisors were randomly divided into six groups with 16 specimens in each: In group 1 (control), brackets were bonded with Transbond™ XT primer. In the experimental groups, microsilver (groups 2 and 3) and nanosilver (groups 4–6) particles of different sizes were added to Transbond XT primer and li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
26
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 49 publications
(60 reference statements)
5
26
2
Order By: Relevance
“…A study on the addition of copper nanoparticles to orthodontic luting agents reported an increase in bond strength after nanoparticle addition. 23 Blöcher et al 32 evaluated the effect of addition of nano and microparticles of silver to orthodontic adhesive, and reported no significant change in SBS. Akhavan et al 33 evaluated the effect of addition of silver nanoparticles/hydroxyapatite to Transbond XT orthodontic adhesive on SBS to enamel and found that addition of 1% to 5% silver nanoparticles/hydroxyapatite increased the SBS of adhesive, while addition of 10% silver nanoparticles/hydroxyapatite had no favorable effect on bond strength, compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…A study on the addition of copper nanoparticles to orthodontic luting agents reported an increase in bond strength after nanoparticle addition. 23 Blöcher et al 32 evaluated the effect of addition of nano and microparticles of silver to orthodontic adhesive, and reported no significant change in SBS. Akhavan et al 33 evaluated the effect of addition of silver nanoparticles/hydroxyapatite to Transbond XT orthodontic adhesive on SBS to enamel and found that addition of 1% to 5% silver nanoparticles/hydroxyapatite increased the SBS of adhesive, while addition of 10% silver nanoparticles/hydroxyapatite had no favorable effect on bond strength, compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…However, it seems that although their early effectiveness, the release of such active principles tends to reduce overtime. Moreover, some of these agents may induce tooth discoloration; for instance, the release of silver ions or chlorhexidine may often cause anaesthetics appearance when incorporated into orthodontic adhesives [9].…”
Section: )" "Although a Decreased Of Antibacterial Activity After mentioning
confidence: 99%
“…Application of fluoride-releasing composites containing nanofillers, antimicrobial orthodontic band cement with silver nanoparticles, and nanosilver-containing orthodontic adhesive primers has been shown to be effective in inhibiting the bacterial growth around fixed appliances. [ 7 8 ] For removable appliances, addition of nanoparticles to PMMA can impart antimicrobial activity to acrylic plates. Among the available nanoparticles, titanium dioxide (TiO 2 ) serves as a good example, because its antibacterial properties have been demonstrated in various biomaterials.…”
Section: Introductionmentioning
confidence: 99%